THE ANALYSIS OF THE DETERMINANTS OF INFLATION IN INDONESIA 1990-2020 - Putry Puspa Ningtyas; Sitti Retno Faridatussalam (Jurnal Ekonomi, 2023)
Consistent price increases for domestic products and services are indicative of inflation, which is detrimental to economic growth. The purpose of this investigation is to dissect the forces that will have an impact on inflation in Indonesia between the years 1990 and 2020. Ordinary Least Squares (OLS) regression analysis was employed for this study. The study found that while the GDP and the budget deficit both had negative effects on inflation, the Exchange Rate (Exchange), the amount of money in circulation, and the level of bureaucracy all had positive effects